Transforming Elementary Literacy: A Deep-Learning-Oriented FIVES Model for Mindful, Meaningful, and Joyful Learning - Fitri Indriyani; Sri Dewi Nirmala; Ryan Dwi Puspita (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: The study aims to investigate the impact of the deep-learning-oriented FIVES (Facts, Inferences, Vocabulary, Experiences, Summarize) model on reading and writing literacy among fifth-grade students. It specifically examines how the model facilitates the manifestation of mindful, meaningful, and joyful learning principles within the primary educational context Methodology: This study employs a qualitative descriptive approach to analyze the implementation of the deep-learning-oriented FIVES model. Subjects were selected via purposive sampling, involving fifth-grade students at SDN Ramea 1. Data were gathered through systematic observations and field notes, then analyzed using data reduction, display, and conclusion drawing techniques to ensure the credibility and depth of the findings. Main Findings: The implementation of the deep-learning-oriented FIVES model significantly proves to strengthen the principles of mindful, meaningful, and joyful learning. Students are capable of meticulously analyzing texts, connecting material with personal experiences, and exhibiting high enthusiasm during collaboration. This model effectively transforms literacy into a process of deep meaning construction, which enhances both writing quality and students' critical thinking skills. Novelty/Originality of this study: This study advances existing knowledge by integrating the FIVES model with a deep learning approach, specifically emphasizing the synergy between mindful, meaningful, and joyful principles. It provides a transformative pedagogical framework that transcends technical skill acquisition, offering unique strategies for primary educators to cultivate 21st-century literacy competencies through reflective, student-centered, and emotionally resonant classroom ecosystems.